TRANSFORMATION OF JAMMU AND KASHMIR: FROM STATE TO UNION TERRITORY AND IMPLICATIONS FOR LOCAL GOVERNANCE - Shahid Javid; Faheem Ahmad Dar (RADJA PUBLIKA, 2023)
This article examines the historical backdrop and ramifications of the revocation of Article 370 from the Indian Constitution in August 2019. This constitutional provision had conferred special status to the state of Jammu and Kashmir. The historical background of Article 370, examining its inception in relation to the accession of Jammu and Kashmir to India in 1947. The article elucidates the original purpose of Article 370, which was designed as a provisional measure to confer the state with its own constitution and restricted authority in legislative affairs. Nevertheless, as time passed, it evolved into a lasting component of the Indian Constitution, giving rise to ambiguity over the state's affiliation with India. The implementation of Article 35A in 1954, which delineated the privileges of those with permanent residency status, added a layer of complexity to the situation. The following analysis delves into the Jammu and Kashmir Reorganisation Act of 2019, which resulted in the division of the state into two Union Territories, namely Jammu and Kashmir, and Ladakh. This paper examines the changes made to the constitutional framework, executive powers, and legislative body of Jammu and Kashmir subsequent to the process of reorganisation. This study examines the implications of Panchayat Raj Institutions (PRIs) in the Union Territory, with a particular focus on the need of structural changes, the mitigation of violence, and the successful execution of the 73rd and 74th Amendments to enhance the authority of local administration in the area.